Enlarging rodent diversity in west-central Argentina: a new species of the genus Holochilus (Cricetidae, Sigmodontinae) - Pardiñas, Ulyses Francisco José (2013)
On the basis of an adult individual collected in 1955 plus 3 mandibles of latest Holocene age, we describe a new living species of the amphibious rat Holochilus (Sigmodontinae, Oryzomyini) from west-central Mendoza Province, Argentina. The new species is characterized by its short tail, broad zygomatic plate with rounded anterior-superior corner, bony palate without excrescences, large mesolophostyle in the upper first molars and complex upper third molar shorter than the second, and lacking the hypoflexus. The morphological traits displayed by this new Holochilus combine features observed in both the H. brasiliensis and H. sciureus groups with others unique among the genus (e.g., absence of hypoflexus). This new species is the southernmost expression of the genus along the western side of its current range, where it appears isolated in the middle part of the Río Atuel. The finding reported here uncovers and highlights unexpected diversity in southern South American arid lands.